Effects of cooking and extra virgin olive oil addition on bioaccessibility of carotenes in tomato sauce - Tomas, Merve; Sagdic, Osman; Catalkaya, Gizem; Kahveci, Derya; Capanoglu, Esra (Tubitak Scientific & Technological Research Council Turkey, 2019)
In this study, the effects of cooking and the addition of extra virgin olive oil on the in vitro bioaccessibility of carotenoids in tomato sauce were evaluated. The results indicated that total antioxidant activity, alpha-tocopherol, lycopene, beta-carotene, lutein, and chlorophyll a contents were positively affected by the combination of cooking and addition of extra virgin olive oil. Moreover, after in vitro digestion, for intestinal phase, lycopene and beta-carotene were observed in all samples, whereas alpha-tocopherol and chlorophyll a were not detected in any of the samples. Lycopene (approximate to 8.5-fold) and beta-carotene (approximate to 5-fold) were significantly improved (P < 0.05) by the effect of cooking and addition of extra virgin olive oil to the samples compared to control tomato sauce (without oil and cooking).
Keywords: Carotenoids; extra virgin olive oil; food matrix; antioxidant; in vitro bioaccessibility; IN-VITRO BIOACCESSIBILITY; BETA-CAROTENE; INTESTINAL-ABSORPTION; LYCOPENE; DIGESTION; LUTEIN; BIOAVAILABILITY; VEGETABLES; LIPIDS; Agriculture; Forestry